Super SeederAdvancing climate-resilient agricultural technology - Kumar, Devesh; Meena, Vijay Singh; Singh, Arvind Kumar (Indian Farming, 2024)
Adoption of Super Seeder, increases overall productivity and reduces cultivation costs. Many farmers burn crop residues after harvesting, causing environmental pollution and soil fertility depletion. The Super Seeder addresses this issue by managing crop residues, preparing land, and sowing seeds in a single pass, saving time and enhancing efficiency.